HOST RESISTANCE IN COCONUT LEAVES AGAINST LEAF BLIGHT DISEASE CAUSED BY PESTALOTIOPSIS PALMARUM (COOKE) STEY - A. Karthikeyan; R. Bhaskaran (International Coconut Community Journal, 1997)
Total and Ortho dihydroxy were more in younger coconut leaves as compared to the older leaves. Seven phenolic compounds were detected in younger leaves while the older leaves had only six phenolic compounds except chlorogenic acid Phenolic compounds inhibited the mycelial growth and Sporulation of P. palmarum. The quantity of sugars, starch and cellulose were lesser in younger leaves. Carbohydrates increased the mycelial growth and sporulation of the pathogen.